Serum soluble triggering receptor levels expressed on myeloid cells2 identify early acute kidney injury in infants and young children after pediatric cardiopulmonary bypass - Sun, Mingwei; Yang, Lijun; Zong, Qing; Ying, Liyang; Liu, Xiwang; Lin, Ru (Frontiers in Pediatrics, 2023)
Acute kidney injury (AKI) after cardiopulmonary bypass (CPB) is a potential complication of pediatric cardiac surgery and contributes a certain amount of perioperative mortality. Serum soluble triggering receptor expressed on myeloid cells2 (sTREM2) is an inflammation-associated cytokines in circulation. Alterations of sTREM2 level have been reported in Alzheimer’s disease, sepsis and some other pathologic conditions. This study aimed to investigate early renal injury in infants and young children after CPB and the role of sTREM2 as a predictor for AKI after CPB. A prospective cohort study was performed in an affiliated university children’s hospital with consecutive infants and young children undergoing CPB from September 2021 to August 2022. These patients were classified into an AKI group (n=60) and a non-AKI group (n=10). Patient demographics and clinical characteristics were analyzed. STREM2 levels were measured during perioperative period with enzyme-linked immunosorbent assay (ELISA). In children developing AKI, the sTREM2 levels significantly decreased at the beginning of CPB compared to the non-AKI group. Based on multivariable logistic regression analysis, risk adjusted classification for congenital heart surgery (RACHS-1) , operation time and the s-TREM2 level at the beginning of CPB had Operation time, RACHS-1 score, and sTREM2 level at the beginning of CPB were independent prognosis factors of post‑CPB AKI. Decreased sTREM2 identifies post-CPB AKI in infants and young children, and ultimately hampered the outcomes. The findings suggest that sTREM2 in pediatric CPB patients may be a protective factor for AKI after CPB.